2013
DOI: 10.3233/jad-2012-120865
|View full text |Cite
|
Sign up to set email alerts
|

β-Asarone Inhibits Neuronal Apoptosis via the CaMKII/CREB/Bcl-2 Signaling Pathway in an in vitro Model and AβPP/PS1 Mice

Abstract: β-Asarone, an active component of the Acori graminei rhizome that has been used as traditional Chinese herb, has been reported to be capable of inhibiting neuronal apoptosis. However, the signaling mechanism underlying the inhibitory effect of β-asarone has remained elusive. This study was aimed to investigate whether the CaMKII signaling pathway is involved in the β-asarone mediated neuroprotection. Using PC12 cells and primary cultures of cortical neurons treated with amyloid-β (Aβ)(1-40) or Aβ(1-42) peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 50 publications
3
56
0
Order By: Relevance
“…Pharmacological studies have proved that aasarone has effect on central nervous inhibitory, and was applied in epilepsy, asthma, and depression treatment (Lee et al 2014;Lu et al 2014;Huang et al 2013;Su et al 2014). However, the neuroprotective effects of b-asarone were highly suggested in recent studies, especially in AD investigation (Zou et al 2011;Liu et al 2010;Geng et al 2010;Wei et al 2013). Our previous studies have also suggested that b-asarone could inhibit neuronal apoptosis and improve memory deficits in Tg AD-model mice.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Pharmacological studies have proved that aasarone has effect on central nervous inhibitory, and was applied in epilepsy, asthma, and depression treatment (Lee et al 2014;Lu et al 2014;Huang et al 2013;Su et al 2014). However, the neuroprotective effects of b-asarone were highly suggested in recent studies, especially in AD investigation (Zou et al 2011;Liu et al 2010;Geng et al 2010;Wei et al 2013). Our previous studies have also suggested that b-asarone could inhibit neuronal apoptosis and improve memory deficits in Tg AD-model mice.…”
Section: Discussionmentioning
confidence: 86%
“…b-asarone, the essential component of Acori graminei rhizoma (AGR), can easily pass through BBB (Fang et al 2012) and exert neuroprotective effects in both vivo and vitro AD models (Zou et al 2011;Liu et al 2010;Geng et al 2010). Our previous study has proven that b-asarone could reduce neuronal apoptosis and improve memory deficits in Tg AD-model mice (Wei et al 2013). In the present study, we evaluated the effects of b-asarone on amyloidosis in b-amyloid precursor protein and presenilin-1 (APP/PS1) double Tg AD-model mice, and the results showed that b-asarone could improve the survival of neurons of APP/PS1 mice, and in the meanwhile, decrease Ab deposition and Ab1-42 level in the hippocampus and cortex of APP/PS1 mice brain.…”
Section: Introductionmentioning
confidence: 93%
“…Bcl-2 might have neuronal anti-apoptotic and neuroprotective effects (Manji et al, 2000;Lei et al, 2012;Wei et al, 2013). Oxidative stress causes brain damage in bipolar patients (Wang et al, 2009); therefore, Bcl-2 levels in bipolar patients in a manic phase might decrease.…”
Section: Discussionmentioning
confidence: 97%
“…The anti-apoptotic protein Bcl-2 prevents mitochondrial release of cytochrome c, which leads to apoptosis (Scorrano and Korsmeyer, 2003;Ohkubo et al, 2007). In addition, Bcl-2 may inhibit neuronal apoptosis and has a neuroprotective effect (Chen et al, 1997;Manji et al, 2000;Lei et al, 2012;Wei et al, 2013). Anti-apoptotic protein Bcl-2 may play a role in the pathophysiology of bipolar disorder (Benes et al, 2006;Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…β-asarone can easily pass through the blood brain barrier (BBB) [14] and substantial experimental evidence indicates that β-asarone is the active ingredient for attenuating learning and memory deficits [1517]. Moreover, β-asarone could alleviate cognitive impairments in Parkinson’s disease [13], Alzheimer’s disease [18, 19], and neuroinflammatory [20], etc. Traditional use and clinical reports showed that β-asarone is effective for the treatment of learning and memory deficits, so we hypothesized that it may manage memory impairments following chronic Pb exposure.…”
Section: Introductionmentioning
confidence: 99%